Pelatihan Pengolahan Limbah Organik Rumah Tangga dengan Budidaya Maggot Black Soldier Fly (BSF) kepada IRT RT 08 RW 14 Jatisampurna, Kota Bekasi - Wahyuningrum, Maria Aditia; Suryani, Suryani; M. Sholihah, Siti; Muhdiana, Ludi; Romayanti, Angelina; Alifya, Adila Tsabita (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Household organic waste management in Indonesia remains a serious challenge, with food scraps being the largest component of waste. Limited knowledge among the community, particularly housewives, about effective and economically valuable processing methods is a major challenge. This study aims to empower housewives in RT 08 RW 14 Jatisampurna, Bekasi City through Black Soldier Fly (BSF) maggot cultivation training as a solution for organic waste bioconversion. The activity was carried out from June to September 2025. The methods used were counseling, training, and practical mentoring. The results of the activity showed a 76% increase in participant knowledge based on pre- and post-activity tests. The